Age-Friendly Cities of Europe - Green, Geoff (Springer US, 2012)
This article summarizes how members of the European Healthy Cities Network have applied the ‘healthy ageing’ approach developed by the World Health Organization in their influential report on Active Ageing. Network Cities can be regarded as social laboratories testing how municipal strategies and interventions can help maintain the health and independence which characterise older people of the third age. Evidence of the orientation and scope of city interventions is derived from a series of Healthy Ageing Sub-Network symposia but principally from responses by 59 member cities to a General Evaluation Questionnaire covering Phase IV (2003–2008) of the Network. Cities elaborated four aspects of healthy ageing (a) raising awareness of older people as a resource to society (b) personal and community empowerment (c) access to the full range of services, and (d) supportive physical and social environments. In conclusion, the key message is that by applying healthy ageing strategies to programmes and plans in many sectors, city governments can potentially compress the fourth age of ‘decrepitude and dependence’ and expand the third age of ‘achievement and independence’ with more older people contributing to the social and economic life of a city.